Effect of acute static stretching duration on isokinetic peak torque in pubescent soccer players - Zakas, A.; Doganis, G.; Galazoulas, C.; Vamvakoudis, E. (Pediatric Exercise Science, 2006)
Although athletes routinely perform warm-up and stretching exercises, it has been suggested that prolonged stretching immediately before an activity might negatively affect the force production. Sixteen male pubescent soccer players participated in the study to examine whether a routine duration of acute static stretching is responsible for losses in isokinetic peak torque production. All participants performed two static stretching protocols in nonconsecutive training sessions. The first stretching protocol was performed three times for 15 s (volume 45) and the second 20 times for 15 s (volume 300). Range of motion (ROM) was determined during knee flexion with the use of a goniometer. The peak torque of the dominant leg extensors was measured on a Cybex NORM dynamometer at various angular velocities. The statistical analysis showed that peak torque did not change following the static stretching for 45 s in all angular velocities, while it decreased (p < .001) in all angular velocities following the static stretching for 5 min. The findings suggest that strength decreases after static stretching exercises may be the result of the performed stretching duration.